Energy metabolism of follicular environment during oocyte growth and maturation - LIPINSKA, Paulina; WARZYCH, Ewelina (Journal of Reproduction and Development, 2020)
Oocyte quality is affected by many factors, among which the environment of growth and maturation seems to be crucial. Studies show that well balanced oocyte energy metabolism has a significant impact on several elements of cytoplasmic and nuclear maturation as well as further embryo developmental competence. Therefore homeostasis between metabolism of glucose and fatty acids in the oocyte is being widely described nowadays. This review aims to discuss the follicular (in vivo) or maturation media (in vitro) environments with regard to glucose and fatty acid metabolism, as the main sources of the energy for the oocyte. A great emphasis is given on the balance between those two metabolic pathways and its further impact on female fertility.